Feasibility Test for Multimedia Learning in Mu'allimin Muhammadiyah Madrasah of Yogyakarta, Indonesia - Arqam, Muhammad Lailan (Budapest International Research and Critics University, 2019)
This study discusses about the feasibility test for multimedia learning in Mu’allimin Muhammadiyah madrasah of Yogyakarta, Indonesia. The results shows that the multimedia developed has an attraction that can bring out and increase student interest and motivation. While a total of 26 students in other words a total of 87% of the trial subjects used chose the